Privatization of migration control : power without accountability? - Sarat, Austin (Emerald Publishing Limited, 2021)
This special issue is the second of a two-part edited collection on the privatization of migration. The central thrust of the special issue is a critical analysis of modern day manifestations of private participation in immigration control such as through companies which run detention and deportation programmes and individual landlords, medical professionals and employers who become -- Part of immigration enforcement. In the chapters the authors examine the role of private stakeholders and the political economy in migration control.
Keywords: Emigration and immigration law.; Privatization.; Immigration enforcement.; Law, Emigration & Immigration.; Citizenship & nationality law.; elektronické knihy; electronic books